2023
DOI: 10.2147/idr.s405816
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Genomic Characteristics of Hypervirulent Klebsiella pneumoniae in a Tertiary Care Hospital, Eastern India

Abstract: Purpose This study was conducted to find out the occurrence of hypervirulent Klebsiella pneumoniae (hvKP) isolates from different clinical specimens in a tertiary care hospital of eastern India and investigate the distribution of virulence factors, capsular serotypes and antibiogram profile. The distribution of carbapenemase-encoding genes in convergent (hvKP and carbapenem-resistant) isolates was also studied. Materials and methods A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…In a study from Eastern India, the most frequent capsular serotypes identified were K1, K2, K5, K20, K54, and K57. The same study noted a 3.3% prevalence of hvKp strains, with more than 50% of them showing bla OXA-48 and bla OXA-181 [26]. In the present study, KL51, KL64, and KL17 capsular serotypes were predominant.…”
Section: Figure 1: Klebsiella Pneumoniae Colony Textures After Being ...supporting
confidence: 67%
“…In a study from Eastern India, the most frequent capsular serotypes identified were K1, K2, K5, K20, K54, and K57. The same study noted a 3.3% prevalence of hvKp strains, with more than 50% of them showing bla OXA-48 and bla OXA-181 [26]. In the present study, KL51, KL64, and KL17 capsular serotypes were predominant.…”
Section: Figure 1: Klebsiella Pneumoniae Colony Textures After Being ...supporting
confidence: 67%
“…Reports from India have highlighted the presence of hvKP, particularly in nosocomial settings, exhibiting drug resistance. However, these studies have primarily relied on phenotypic and biochemical methods rather than genomic analysis [15, 16]. There are also reports of MDR hvKp strains which have been emerging, spawning a new generation of hypervirulent ‘superbugs’ [17, 18].…”
Section: Introductionmentioning
confidence: 99%